Viral Etiology of Acute Respiratory Infections in Pediatric Patients in Lebanon - Khaldoun Masoud; Ghassan Matar; Ghassan Dbaibo; Geoarge F Araj; Hasan Zaraket; Rima Hanna Wakim (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Acute respiratory infections (ARI) are the leading cause of death worldwide especially among children. The majority of these infections in children are of viral etiology. In this study, we evaluated the incidence of viral ARI among children in Lebanon. Methods: Children presenting with symptoms of ARI were prospectively recruited between September 2009 to February 2012. Nasopharyngeal aspirates were obtained from patients and screened for 11 respiratory viruses using a multiplex Luminex-based PCR assay. Results: Two hundred twenty-one patients were recruited with a median age of 1 year (IQR: 0 - 5). Out of 221 patients, 116 (52.5%) were positive for at least one virus, the majority (103/116; 88.8%) of which were in children under 6-year of age. Overall 188 viruses were detected. Rhinovirus (RhV) was the most common virus detected in 81 (69.8%) patients followed by coxsackie virus and echovirus (CVEV) which were detected as one target in the panel in 45 (38.8%), and parainfluenza viruses (PIV types: 1, 2, 3, 4) in 24 (20.7%) patients. Coinfection with more than one virus was detected in 49 (42.9%) patients. RhV and CVEV were the most common viruses associated with co-infections and higher risk of rhinorrhea. Conclusion: Viral pathogens account for at least half of the ARIs in Lebanon, with a high frequency of co-infections being detected.